2012
DOI: 10.1021/la301363d
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Effects of Surfactants on Droplet Formation in Coaxial Microfluidic Devices

Abstract: Droplet emulsification in microfluidic devices involves the constant formation of fresh interfaces between two immiscible fluids. When the multiphase system contains surfactant, dynamic mass transfer of the surfactant onto the interface results in a dynamic interfacial tension different from the static interfacial tension measured in an equilibrium state. In this work, we have systematically investigated the effects of surfactant concentration and type on the dynamic interfacial tension of two different liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 44 publications
6
81
0
Order By: Relevance
“…In our previous work (Xu et al, 2012;Xu et al, 2008), it was shown that the droplet diameter in coaxial microfluidic devices can be estimated by a model at low values of the continuous flow Reynolds number, which is expressed as…”
Section: The Dynamic Interfacial Tension With Varied Droplet Sizesmentioning
confidence: 99%
“…In our previous work (Xu et al, 2012;Xu et al, 2008), it was shown that the droplet diameter in coaxial microfluidic devices can be estimated by a model at low values of the continuous flow Reynolds number, which is expressed as…”
Section: The Dynamic Interfacial Tension With Varied Droplet Sizesmentioning
confidence: 99%
“…An overview of droplet sizes and time-scales in these measurements is given in Table 1.2. (Steegmans, Warmerdam, et al 2009), (B) (Wang, Lu, Xu & Luo 2009), and (C) (Xu et al 2012); pressure drop (D) (Wang et al 2014); and droplet deformation (E) (Brosseau et al 2014). processes.…”
Section: Emulsifier Adsorptionmentioning
confidence: 99%
“…Microfluidic devices can also be used for interfacial tension measurements (Wang, Lu, Xu & Luo 2009;Brosseau et al 2014;Xu et al 2012;Wang et al 2014;Steegmans, Warmerdam, et al 2009). The tensiometric measurements of and Steegmans et al (2009) were both conducted in cross-flow microfluidic devices and were based on the relation between droplet size and interfacial tension; the former is able to measure in the millisecond range and the latter in the sub-millisecond range, due to differences in geometry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations